The Effect of Service Quality on Satisfaction apropos Service Recipients of Divisional Secretariats in Colombo District in Sri Lanka - Nilwala, N.; Gunawardana, K.; Fernando, R.L.S. (Journal o f Management and Sustainability, 2017)
Attached

A vast array o f knowledge has been accumulated on the effect o f service quality on customer satisfaction, particularly with a large number o f studies over the past few years. However, the effect o f service quality on satisfaction of service recipients in Divisional Secretariats in the Public Sector is relatively an unattended area by researchers. Hence, this study was carried out to evaluate the effect o f service quality on satisfaction o f service recipients o f divisional secretariats. This particular organization was selected for the study as it is considered to be the most significant service provider in terms o f statutory, social, economic and development in the country. A questionnaire survey and personal interviews were conducted to collect data by using the purposive sampling method. A modified questionnaire was prepared based on SERVQUAL instruments with two additional questions. A sample o f 520 service recipients from 13 Divisional Secretariats in Colombo was drawn and it was represented by 40 from each division. Correlation analysis and multiple regression analysis were used to examine the relative impact o f the service quality on satisfaction o f service recipients. The study revealed that all the service quality attributes positively related to satisfaction o f the service recipients. The findings o f the study show that satisfaction o f service recipients in terms o f service quality has not met the expected level, which a divisional secretariat is deemed to provide for.
Keywords: service quality; service recipient; Divisional Secretariat; satisfaction